Status of seawater intrusion in Mexico: A review - Xiaoxiao Zha; Jesús Horacio Hernández Anguiano; Francisco Padilla Benítez; Arturo Cruz-Falcón; Raul Miranda-Avilés; Manuel E. Mendoza Cantú; Jorge Adrian Perera-Burgos; Xu Liao; Juan Manuel Navarro-Céspedes; Miguel Angel Acosta-Reyes; Yanmei Li (Journal of Hydrology: Regional Studies)
Study region: This review examines seawater intrusion in Mexico's coastal aquifers. Study focus: The review synthesizes current knowledge on seawater intrusion in Mexican coastal aquifers, documented since the 1980s. The study shows case studies including the extent of seawater intrusion, driving forces, and mitigation strategies. It reviews the commonly used approaches of seawater intrusion assessment in Mexico. The study discusses how climate change and sea level rise impact coastal groundwater resources. New hydrological insights for the region: Seawater intrusion has been documented in Mexican coastal states since the 1970s. Researchers focused on the Baja California Peninsula, Sonora, and the Yucatán Peninsula. Groundwater analysis reveals diverse intrusion patterns, with below-sea-level water tables extending up to 60 km inland and depths reaching −100 m in Sonora, while the Yucatán Peninsula maintains water tables above sea level. Each region presents distinct research priorities: Baja California faces severe water scarcity due to its arid climate, prompting strategies for water allocation and conservation; Baja California Sur emphasizes climate change impacts on water systems; Sonora's diverse geology necessitates advanced hydrogeological analysis to understand groundwater flow; and Quintana Roo faces heightened vulnerability to sea-level rise, particularly in tourist and ecological zones. This synthesis of seawater intrusion highlights the role of climate change, which directly links to human-induced pressures. The findings offer insights into coastal regions worldwide grappling with similar challenges from climate change and increasing water demand.